2018
DOI: 10.3389/fphys.2018.01677
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of E93 and Kr-h1 in Metamorphosis of Nilaparvata lugens

Abstract: Metamorphosis is a crucial process in insect development. Ecdysone-induced protein 93 (E93) is a determinant that promotes adult metamorphosis in both hemimetabolous and holometabolous insects. Krüppel-homolog 1 (Kr-h1), an early juvenile hormone (JH)-inducible gene, participates in JH signaling pathway controlling insect metamorphosis. In the current study, an E93 cDNA (NlE93) and two Kr-h1 cDNA variants (NlKr-h1-a and NlKr-h1-b) were cloned from Nilaparvata lugens (Stål), one of the most destructive hemimeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 51 publications
2
48
0
1
Order By: Relevance
“…At the same time point (i.e., day four of the fifth nymphal stage (N5 D4)), very significantly upregulated SgKr-h1 transcript levels were detected in dsSgE93 -injected locusts in head and fat body samples ( Figure 3 B). Indeed, Kr-h1 is an early JH response gene, which has been reported in several insect species to mediate the metamorphosis-inhibiting status quo action downstream of the JH signal and its receptor Met [ 7 , 9 , 11 , 13 , 31 , 32 ]. Kr-h1 levels normally drop in the final nymphal stage, when JH titers are low, to ensure a final transition to the adult stage [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time point (i.e., day four of the fifth nymphal stage (N5 D4)), very significantly upregulated SgKr-h1 transcript levels were detected in dsSgE93 -injected locusts in head and fat body samples ( Figure 3 B). Indeed, Kr-h1 is an early JH response gene, which has been reported in several insect species to mediate the metamorphosis-inhibiting status quo action downstream of the JH signal and its receptor Met [ 7 , 9 , 11 , 13 , 31 , 32 ]. Kr-h1 levels normally drop in the final nymphal stage, when JH titers are low, to ensure a final transition to the adult stage [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting JH-Met-Tai complex induces the expression of JH response genes, including the gene coding for Krüppel-homolog 1 ( Kr-h1 ), a Zn-finger containing transcription factor [ 5 , 6 ]. RNA interference (RNAi) studies have demonstrated the importance of the JH receptor Met, as well as the downstream-acting transcription factor Kr-h1, in mediating the anti-metamorphic effects of JH in the red flour beetle Tribolium castaneum , the German cockroach Blattella germanica , the kissing bug Rhodnius prolixus , the two-spotted cricket Gryllus bimaculatus , the brown planthopper Nilaparvata lugens , the common bed bug Cimex lectularius , the migratory locust Locusta migratoria and the fire bug Pyrrhocoris apterus [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Met‐Kr‐h1‐E93 pathway (MEKRE93 pathway) appears to be central to the status quo action of JH in which E9 3 acts downstream of Kr‐h1 to promote adult metamorphosis (Belles and Santos, ; Ureña et al, ). For instance, the knockdown of Kr‐h1 with RNAi in N. lugens resulted in significant up‐regulation of E93 (Li et al, ). Further research is required to identify the molecular mechanism underlying the role of Kr‐h1 in the reproduction of C. suppressalis .…”
Section: Discussionmentioning
confidence: 99%
“…In other holometabolous insects including beetle Tribolium castaneum , moths Bombyx mori and Helicoverpa armigera , as well as hemimetabolous insects including cockroach Blattella germanica , planthopper Nilaparvata lugens , and stinkbug Pyrrhocoris apterus and Rhodnius prolixus , Kr-h1 has also exhibited anti-metamorphic effects ( Minakuchi et al, 2009 ; Konopova et al, 2011 ; Lozano and Belles, 2011 ; Kayukawa et al, 2017 ; Li et al, 2018 ; Zhang W. N. et al, 2018 ).…”
Section: Diverse Roles Of Sesquiterpenoids In Insectsmentioning
confidence: 99%